The relationship between fuel, biofuel and food prices: Methods and outcomes - Karel Janda; Ladislav Krištoufek (Charles University in Prague, Institute of Economic Studies (IES), 2018)
We assess the fuel-food price linkage models of the structural and of the time series nature with the main attention devoted to the time series literature. We document shifting focus from a straightforward vector autoregressive and error-correction analysis of fuel-food commodity price level co-movement towards inclusion of biodiesel and ethanol prices directly into analysis, towards consideration of both price levels and price volatilities, and towards growing sophistication of econometric methodologies and integration of econometrics of price co-movement with theoretical considerations. The key insight of biofuels price transmission literature is that the price transmission is time and market specific, evolving with the development of biofuels policies and technologies. The most prominent relationships are coming from oil to agricultural commodities and then towards biofuels. While here are also studies not finding any strong connection between biofuels and their feedstock, the literature finding biofuels driving the prices of agricultural commodities up is negligible.
Keywords: Q16; Q42; Q56; 330; biofuels; fuels; food; ethanol; biodiesel; oil